On the design of steel lattice telecommunication towers - Abdalla, K. M.; Efthymiou, E.; Baniotopoulos, C.C. (Journal of Structural Engineering, 2024)
The herein presented research work investigates the structural performance of steel telecommunication towers considering that their structural integrity is their most important design criterion. To this end, the contemporary normative framework regarding the actions on these structures is presented, analysing particularly the wind effects being the predominant loading cases and highlighting the basic aspects of the finalised provisions of Eurocodes. The study involves the analysis of certain types of lattice telecommunication structures which are located either on the ground, or on the top of buildings. In this framework, the response of these steel lattice towers under the main action of wind, as well as the combined environmental effect is thoroughly examined, thus contributing to the broadening of knowledge regarding their structural behaviour. Finally, given the large amount of existing telecommunication infrastructure that was constructed according to old regulations, strengthening options are proposed which are numerically verified in line with the contemporary relevant codes.